Individual differences in emotional regulation: how do executive functions influence on differential outcomes of emotional regulation - Wong, Yu Fung (Nanyang Technological University, 2025)
This study explores the relationships between executive functions and emotional regulation strategies, specifically focusing on reappraisal and distraction, in the context of varying emotional intensities. Utilizing an experience sampling method and an emotional regulation Choice paradigm, we aimed to understand how executive functions influences individuals’ preferences for emotional regulation strategies when faced with negative emotions. Despite hypothesized links between executive functions and emotional regulation outcomes, our analyses did not support significant relationships, suggesting that executive functions may not directly impact emotional outcomes as anticipated. Interestingly, findings indicated that participants preferred not to engage in emotional regulation strategies for low-intensity negative stimuli, while they actively sought regulation strategies for high-intensity stimuli. These results suggest that perhaps there are other factors at high levels of executive function which significantly affect emotional regulation. Future studies should consider a broader range of emotional regulation strategies and refine executive function measurement approaches to better capture the nuances of these relationships.